IMPLEMENTASI KAMUS KATA SERAPAN BAHASA INDONESIA – INGGRIS DENGAN FITUR AUTO COMPLETE TEXT MENGGUNAKAN ALGORITMA INTERPOLATION SEARCH UNTUK SMARTPHONE BERBASIS ANDROID - Muhammad Hatta; Sutardi Sutardi; Bambang Pramono (semanTIK, 2016)
Loan words are words derived from foreign languages that have been integrated to a language and their  use is generally accepted. To some people, the pronounciation of those words may have some errors caused by lack of understanding of the words. In addition, loan words are used by many areas of work. Therefore, a system that display the words and their meanings is needed. An effective algorithm or method is needed to develop search dictionary application because data search is an important part in data processing. This application uses Interpolation Search algorithm. Interpolation search algorithm is more  efficient than Binary  Search  and Sequential Search. The reason behind this is because the algorithm does not need to access each  tabel’s elements. The translated words have Text Auto Complete feature to facilitate users to find the desired words. The result of this research is the implementation of Indonesian-English loan words dictionary application to Android Operating System that is developed using Android Programming Language. Keywords—Loan words, Interpolation Search, Text Auto Complete, Android